Democracy in the Sheets, Ethnonationalism in the Streets: Acquiescent Integration Strategy of Immigrants from the Former Soviet Union in Israel - Kerez, Sasha (Tufts Archival Research Center, 2017)
Immigrants from the former Soviet Union (FSU) in Israel believe in the tenets of the classic assimilation theory, which posits that immigrant integration is a one-directional process during which the incoming population changes to become indistinguishable from the domestic population. This belief stems from their socialization in the FSU and their resulting understanding of democratic governance as having a strict separation between public and private spheres. FSU immigrants believe that a democratic government must safeguard the rights of citizens to hold onto non-dominant identities in the private sphere, but that it is also entitled to demand loyalty to the state’s dominant ethos in the public sphere. These attitudes result in their non-mobilization and acquiescence even in the face of discrimination. In addition to placing demands for acquiescence onto themselves, FSU immigrants place these demands onto Israel’s Arab minority and espouse nativist attitudes toward them, when they fail to subscribe to the acquiescent integration strategy. Thus, this research identifies mechanisms underlying not just their integration, but also their racial distancing from Arab Israelis. It also contributes to immigrant integration theory by highlighting the importance of basing integration theory not only on cases in the US, but also in countries in which citizenship is allocated on a jus sanguinis basis. The study also deepens the understanding of political attitudes of the Russian-speaking community in Israel so that people and organizations wishing to work with this community, especially regarding its experiences with maltreatment, can devise more tailor-made programs.